The Importance of Language of Leadership in the Academic Enterprise The case of : Ihssen Academy Laghouat - Ferhat ,Soumaya; Nouioua ,Amira Hiba (University of Ammar Theledji -Laghouat, 2020)
Language, for leaders, is a vehicle for making decisions, resolving disputes, enacting practices, measuring results, and sharing innovation and creativity. However, for educational leaders, the “language of leadership” is considered a crucial emphasis in developing the educational organization. The dissertation aims to examine the position of the language of leadership in the academic enterprise, namely Ihssen Academy Laghouat as a case study, and whether the academic staff there is aware of its importance. If “yes”, how do the educational leaders in that particular academy use it? Consequently, the results of this research have induced an interrelation between the language of leadership, academic enterprise, and effective educational outcomes. The thesis concludes, according to action research, that the concept of the language of leadership in the academic enterprise exists mainly thanks to the prioritization of teachers’ professional training. Eventually, the function of “the language of leadership” in the academic enterprise is to enhance student learning achievement and staff performance